Characterisation of single use scrub suits using a thermal manikin - Ribeiro, Patrícia (2014)
Over the last years scrub suits were gaining acceptance in the healthcare institutions and today are the most used materials for single-use medical clothing. Being the most used medical clothing by health professionals, scrub suits must be comfortable. The purposes of this paper is the study of thermal comfort regarding twelve commercially available scrub suits and relate the properties to determine some conclusions about the importance of thermal comfort in this specific clothing systems. Thermal properties were evaluated using a thermal dry manikin that simulates human body temperature.